No retinopathy after orbital irradiation in patients with thyroid eye disease – a follow up study - Makhoul, Sara; Aranyosi, Janos K.; Csiki, Emese; Urbancsek, Hilda; Nagy, Edit B.; Erdei, Annamaria; Fodor, Mariann; Kovacs, Arpad; Nagy, Endre V.; Ujhelyi, Bernadett (Frontiers in Endocrinology, 2025)
IntroductionThyroid eye disease (TED) is an autoimmune disease of the orbit. In moderate to severe active disease, orbital radiotherapy (ORT) is a treatment option. Diabetes is considered a relative contraindication because of potential induction of retinopathy. The purpose of this study was to decide if ORT remains a risk towards retinopathy in the era of linear accelerators with 3D computer aided design. Follow up examinations were performed to detect radiogenic retinopathy.MethodsOf the 151 patients who received ORT for TED between 2004–2020 at the University of Debrecen, 97 patients were available for follow up. In each case, 3D-based LINAC radiotherapy with a total dose of 20 Gy in 2 Gy daily fractions was administered. Eighteen patients had type 2 and one patient had type 1 diabetes. Median duration of diabetes was 16 (IQR:11.75-17.0) years; most recent HbA1c before irradiation was 6.55 (IQR:6.22-6.95) %. Ophthalmological follow up included slit-lamp and fundus examination, visual acuity, exophthalmometry and clinical activity score (CAS) calculation.ResultsMedian time between TED start and ORT was 2 (IQR:1-8) years. At the time of ORT, median TSH was 0.84 (IQR:0-1.41) mU/L, fT4 18 (IQR:12.15-25.40) pmol/L and fT3 6.5 (IQR:4.4-11.0) pmol/L, CAS was 5 (IQR:4-6). No diabetic retinopathy was present before ORT. The median follow-up period after completion of ORT was 60 (IQR:38-100) months. No patient developed retinopathy.DiscussionThe risk of radiation-induced retinopathy after orbital irradiation, including well controlled diabetic patients, appears to be negligible. In the absence of pre-existing diabetic retinopathy and with good glycemic control ORT might be safe if linear accelerator with 3D planning is used. However, ophthalmic surveillance is still recommended.